The Effect of an Empowerment Program on the Health-promoting Behaviors of Iranian Women Workers: A Randomized Controlled Trial - Fatemeh Noori; Zahra Behboodimoghadam; Shima Haghani; Shahzad Pashaeypoor (Korean Society for Preventive Medicine, 2021)
Objectives The workplace is an ideal place for encouraging health-promoting behaviors. Therefore, the aim of the present study was to determine the effect of an empowerment program on the health-promoting behaviors of women workers. Methods This randomized clinical trial was conducted with 80 women workers employed at a food packaging facility in 2020. The subjects were selected using convenience sampling and were classified into intervention and control groups using block randomization. An empowerment program for women workers was conducted across 6 sessions based on an empowerment model. Data collection tools included a demographic questionnaire and the Health Promoting Lifestyle Profile-II, which participants completed both before the program and 8 weeks after the last session. Data analysis was performed in SPSS version 16 using descriptive analysis and inferential statistics. Results There were no significant differences between the 2 groups in various health-promoting behaviors before the program. However, the intervention group's scores for nutrition (34.92±1.09 vs. 27.87±4.23), physical activity (24.40±2.94 vs. 17.40±5.03), stress management (26.35±2.60 vs. 23.05±4.27), spiritual growth (34.02±3.00 vs. 30.22±5.40), interpersonal relationships (30.82±2.38 vs. 27.60±4.61), and health responsibility (31.60±2.71 vs. 28.22±4.59) were significantly higher than the control group's 8 weeks after the program had ended. Moreover, there was a significant difference in the total score of health-promoting behaviors for the intervention group compared to the control group (179.00±9.22 vs. 151.42±20.25, p=0.001). Conclusions An empowerment program for women workers led to significant improvements in the health-promoting behaviors of the participants. Similar programs can ultimately improve women's health in the workplace.